Stimulation of MMP-1 and CCL2 by NAMPT in PDL Cells - Marjan Nokhbehsaim; Sigrun Eick; Andressa Vilas Boas Nogueira; Per Hoffmann; Stefan Herms; Holger Fröhlich; Søren Jepsen; Andreas Jäger; Joni Augusto Cirelli; James Deschner (Mediators of Inflammation)
Periodontitis is an inflammatory disease caused by pathogenic microorganisms and characterized by the destruction of the periodontium. Obese individuals have an increased risk of periodontitis, and elevated circulating levels of adipokines, such as nicotinamide phosphoribosyltransferase (NAMPT), may be a pathomechanistic link between both diseases. The aim of this in vitro study was to examine the regulation of periodontal ligament (PDL) cells by NAMPT and its production under inflammatory and infectious conditions. NAMPT caused a significant upregulation of 9 genes and downregulation of 3 genes, as analyzed by microarray analysis. Eight of these genes could be confirmed by real-time PCR: NAMPT induced a significant upregulation of EGR1, MMP-1, SYT7, ITPKA, CCL2, NTM, IGF2BP3, and NRP1. NAMPT also increased significantly the MMP-1 and CCL2 protein synthesis. NAMPT was significantly induced by interleukin-1β and the periodontal microorganism P. gingivalis. NAMPT may contribute to periodontitis through upregulation of MMP-1 and CCL2 in PDL cells. Increased NAMPT levels, as found in obesity, may therefore represent a mechanism whereby obesity could confer an increased risk of periodontitis. Furthermore, microbial and inflammatory signals may enhance the NAMPT synthesis in PDL cells and thereby contribute to the increased gingival and serum levels of this adipokine, as found in periodontitis.